The Impact of Parasites on Health and Productivity of Cattle in Indonesia Smallholder Farms: Risk Factors and Prevention Strategies - Ani, Ajeng; Masri, Medina (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Cattle in Indonesia possess high reproductive potential, yet the widespread presence of parasites poses a serious threat to their health and productivity. The majority of cattle (99.81%) are traditionally managed by smallholder farmers, often leading to overlooked parasite management. Fascioliasis, caused by the genera Fasciola, Fascioloides, and Dicrocoelium, is a primary parasitic disease that hinders productivity, triggering reproductive disorders, stunted growth, and even mortality. Economic losses attributed to this disease were estimated at 500 billion rupiah annually in 1991, with prevalence once reaching 90%. This journal review synthesizes information from various literature, including journals, notes, and reports pertinent to the impact of parasites on cattle health and productivity in Indonesian smallholder farms. Indonesia's warm and humid tropical climate significantly supports the development of infective worm eggs and larvae. The importance of identifying risk factors and formulating effective prevention strategies is emphasized to optimize cattle productivity and mitigate socio-economic losses caused by parasites.